2003
DOI: 10.1097/00004647-200301000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Spreading Depression Causes a Long-Lasting Decrease in Cerebral Blood Flow and Induces Tolerance to Permanent Focal Ischemia in Rat Brain

Abstract: Cortical spreading depression (CSD) has previously been shown to induce tolerance to a subsequent episode of transient cerebral ischemia. The objective of the present study was to determine whether CSD also induces tolerance to permanent focal ischemia and, if so, whether tolerance may be mediated by alterations in cerebral blood flow (CBF). Sprague-Dawley rats were preconditioned by applying potassium chloride to one hemisphere for 2 hours, evoking 19 +/- 5 episodes of CSD (mean +/- SD, n = 19). Three days la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 18 publications
5
34
0
Order By: Relevance
“…We also showed that pAMPKa is increased only at 24 h after CSD (no modification was seen at 2 and 4 h) suggested a potential link between CSD and neuroprotection through the fine-tuning of AMPK activation by modifying its phosphorylation state only after long-time after CSD induction. This is in agreement with previous studies showed that CSD enhances the ischemic tolerance to temporary focal ischemia after 24 h [12][13][14][15][16][17][18]. Moreover studies on gene expression data, based on time points similar to the present work, show that some genes start to modify their expression relatively late from the induction of CSD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also showed that pAMPKa is increased only at 24 h after CSD (no modification was seen at 2 and 4 h) suggested a potential link between CSD and neuroprotection through the fine-tuning of AMPK activation by modifying its phosphorylation state only after long-time after CSD induction. This is in agreement with previous studies showed that CSD enhances the ischemic tolerance to temporary focal ischemia after 24 h [12][13][14][15][16][17][18]. Moreover studies on gene expression data, based on time points similar to the present work, show that some genes start to modify their expression relatively late from the induction of CSD.…”
Section: Discussionsupporting
confidence: 93%
“…In humans, the CSD waves have also been reported, in particular in brain-injured patients [6,10] and in slices made from surgically removed brain tissue of patients [11]. Moreover, when CSD is induced 24 h prior to an artery occlusion (CSD-preconditioning), it enhances the ischemic tolerance to temporary focal ischemia, with a reduction in the size of the infarcted tissue [12][13][14][15][16][17][18]. The mechanism underlying such neuroprotection induced by CSD remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The protective mechanism of ischemic preconditioning are reported to involve intracellular signal transduction pathway including endoplasmic reticulum and DNA repairing function (Saito et al, 2004;Hayashi et al, 2003;Sugawara et al, 2001). The relationship between preconditioning, induced by spreading depression, and the rCBF just before focal ischemia was reported to be relate to protective mechanisms of ischemic tolerance (Otori et al, 2003). However, the precise mechanism of ischemic tolerance is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…However, a change in extracellular pH within the dura remains to be demonstrated. Cortical spreading depression, which may contribute to migraine headache through activation of the trigeminovascular system, 79,80 was found to be associated with a decrease in dural blood flow 81,82 as well as cortical hypoxia, 80,82,83 events that may decrease the pH of the cortex and/or meninges.…”
Section: Ion Channels and Dural Afferent Activationmentioning
confidence: 99%